Little Miss Sunshine [videorecording (DVD)] - Dayton, Jonathan; Faris, Valerie; Breslin, Abigail, 1996-; Kinnear, Greg, 1963-; Dano, Paul, 1984-; Arkin, Alan (20th Century Fox Home Entertainment, 2006)
Olive is a little girl who dreams of winning the Little Miss Sunshine contest. Her family wants her dream to come true, but they are so dysfunctional that they can barely make it through a day without some disaster befalling them. Olive's father, Richard, is unsuccessful as a motivational speaker. He is barely on speaking terms with Olive's mother. Her uncle Frank has attempted suicide following an unsuccessful romance with a male graduate student. Her brother Dwayne, a fanatical follower of Nietzsche, has taken a vow of silence. And Olive's grandfather is a loser with a drug habit, but at least he enthusiastically coaches Olive in her contest talent routine. Circumstances conspire to put the entire family on the road together with the goal of getting Olive to the Little Miss Sunshine contest in California.